Analyzing Miniso's Marketing Strategy in Attracting Muslim Generation Z Consumers: A Case Study in Parepare, Indonesia - Ardanyar Syahar; Multazam Mansyur Addury; Rusnaena Rusnaena; Sulkarnain Sulkarnain; Arwin Arwin; Mawardi Jalil Masri (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
This study aims to analyze the marketing strategies implemented by Miniso in attracting Muslim Generation Z consumers in Parepare. The research focuses on product strategy, pricing, promotion, location, distribution, service, transaction processes, and the physical appearance of the store. This study employed a descriptive qualitative approach, with data collected from responses provided by Muslim Generation Z consumers, store employees, and the store manager of Miniso. The data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that Miniso attracts Muslim Generation Z consumers through products that are cute, aesthetic, unique, functional, and aligned with current trends. The pricing strategy is perceived as affordable and proportional to product quality. Promotional activities are conducted through social media platforms, including WhatsApp groups, Instagram, and TikTok. Friendly employee service, fast transaction processes, digital payment options, comfortable store design, and attractive product displays also serve as important factors influencing consumer purchase intention. These findings indicate that Miniso’s appeal to Muslim Generation Z consumers is shaped not only by its products but also by a practical, visually engaging, and digitally oriented shopping experience that aligns with the lifestyle and consumption patterns of younger generations.